A culturally sensitive nurse‐led structured education programme in patients with type 2 diabetes. Issue 5 (1st July 2019) - Liu, Yeling; Jiang, Xinjun; Jiang, Hua; Lin, Keke; Li, Mingzi; Ji, Linong
Abstract: Aim: To assess the feasibility, acceptability, and preliminary efficacy of a culturally sensitive nurse‐led structured education programme for patients with type 2 diabetes. Background: A nurse‐led satisfactory diabetes education programme might be feasible. The structured education programme is considered a potential model that helps patients manage diabetes. Design: A mixed‐method design. Methods: A convenience sample of 44 participants received the programme. Feasibility was assessed using the recruitment rate and the retention rate. Acceptability was assessed by interviews to obtain the perception and experience of participants. Also, preliminary efficacy on diabetes knowledge, self‐efficacy, self‐management behaviours, and clinical outcomes was assessed. Finally, data were collected from April to December 2015. Results: The recruitment rate and the retention rate were acceptable. Participants thought that the programme contributed to their positive changes. They enjoyed and accepted the programme, and they wanted to gain the ongoing support. Significant improvements in diabetes knowledge, self‐efficacy, self‐management behaviours, A1C, fasting blood glucose, low‐density lipoprotein cholesterol, weight, body mass index, and waist circumference were reported in 12‐week follow‐up. Conclusions: This programme is feasible and acceptable, and its preliminary efficacy is promising. Ongoing support, a control group, and long‐term follow‐up are required in future studies to assess its effectiveness. SUMMARY STATEMENT: What is already known about this topic? Unsatisfactory diabetes education and a shortage of general practitioners may promote the poor management of patients with type 2 diabetes. Structured education programmes for patients with type 2 diabetes could improve biomedical, psychological, and lifestyle outcomes. A structured education programme for patients with type 2 diabetes without receiving insulin therapy was developed in mainland China. What this paper adds? The structured education programme is feasible and exhibits high preliminary efficacy. Participants received the structured education programme and experienced positive change. Participants hope to gain the ongoing support to maintain self‐management behaviours. The implications of this paper: The study indicates that nurses can use this programme to help patients manage diabetes. The programme can be applied in regular clinic care and generalized to other community health service centres. The results can provide some guidance for the further assessment of the effectiveness of the programme.